Awareness of the 2009 US Preventive Services Task Force recommended changes in mammography screening guidelines, accuracy of awareness, sources of knowledge about recommendations, and attitudes about updated screening guidelines in women ages 40-49 and 50+ - Kiviniemi Marc T; Hay Jennifer L (BMC, 2012)
Abstract Background The US Preventive Services Task Force updated mammography recommendations in 2009, recommending against routine screening for women ages 40-49 and reducing recommended frequency for women 50+. The recommendation changes were highly controversial and created conflicting recommendations across professional organizations. This study examines overall awareness of the changes, accuracy of knowledge about changes, factors related to both overall awareness and accuracy, sources of knowledge about changes, and attitudes about the new recommendations. Method National telephone survey of 508 women, half aged 40-49 and half 50+, conducted one year after the update (November/December 2010; cooperation rate was 36%). Measures include awareness, accuracy, source of knowledge, interactions with providers, and attitudes about the changes. Results Fewer than half of women were aware of the guideline changes. Younger, more educated, and higher income women were more aware. Of those who were aware, only 12% correctly reported both change in age and frequency. Accuracy was not associated with demographics. The majority learned of changes through the media and the majority had negative attitudes about the changes. Conclusions Despite widespread coverage of the recommendation changes, overall awareness in the relevant population is low. Increasing awareness and addressing attitudes about the changes is necessary to ensure the use of recommendations to impact screening behavior.